2015 IEEE International Conference on Electronics, Computing and Communication Technologies (CONECCT) 2015
DOI: 10.1109/conecct.2015.7383934
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-wideband frequency Domain receiver for software defined radio applications

Abstract: This work presents a frequency domain ultrawideband receiver architecture spanning from 500 MHz to 10.5 GHz. Proposed architecture uses Transform Domain (TD) sampling method which relaxes the ADC performance bottleneck for digitizing 500 MHz baseband signal. To achieve wideband operation a RF front end consisting of wideband LNA, VGA, baseband mixer and integrator is designed using UMC 130nm technology. Due to wide frequency operation this architecture is suitable for software defined radio applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, real measurements taken at various times in an urban setting reveal otherwise. It is found that only about 0.5% of available spectrum in the 3-4 GHz frequency band is utilized and in the 4-5 GHz band, the utilization drops to only 0.3% [48]. This is evidence of an abundance of spectrum availability and it shows that the perceived shortage in the spectrum is partially a flaw in the regulatory and licensing process [49,50].…”
Section: Introductionmentioning
confidence: 98%
“…However, real measurements taken at various times in an urban setting reveal otherwise. It is found that only about 0.5% of available spectrum in the 3-4 GHz frequency band is utilized and in the 4-5 GHz band, the utilization drops to only 0.3% [48]. This is evidence of an abundance of spectrum availability and it shows that the perceived shortage in the spectrum is partially a flaw in the regulatory and licensing process [49,50].…”
Section: Introductionmentioning
confidence: 98%
“…For Impedance Definitions, the thickness is as of now represented in the qualities entered (ohms/sqr). There are two strategies, as now and again you know your material conductivity (gold, copper, and so forth) and now and then it is known dielectric material's impedance (thin film resistors, and so on) [14][15][16]. The accompanying names are held and can't be utilized: Air, Perfect Conductor, Approx Open, and Input waveguide.…”
Section: T R a N S A C T I O N S O N N E T W O R K S A N D C O M M U mentioning
confidence: 99%